2016
DOI: 10.3847/0004-637x/832/2/149
|View full text |Cite
|
Sign up to set email alerts
|

r-PROCESS PRODUCTION SITES AS INFERRED FROM Eu ABUNDANCES IN DWARF GALAXIES

Abstract: Recent observations of r-process material in ultra-faint dwarf galaxies (UFDs) shed light on the sources of these elements. Strong upper limits on the Eu mass in some UFDs combined with detections of much larger masses in a UFD, Reticulum II, and other dwarf galaxies imply that Eu production is dominated by rare events, and that the minimal Eu mass observed in any UFD is approximately the amount of Eu mass produced per event. This is consistent with other independent observations in the Galaxy. We estimate,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 94 publications
13
79
0
Order By: Relevance
“…These velocities can be combined with the merger time for the DNS system to estimate the offset distance of the future DNS merger (short GRB) from its birth place in the Galactic disk (e.g. Bloom et al 1999;Perna & Belczynski 2002;Voss & Tauris 2003;Fong et al 2010;Kelley et al 2010;Beniamini et al 2016b). Assuming, as a first-order approximation, constant motion throughout a galactic potential, an upper limit for this distance can be simply estimated as: d pc ≃ v km/s · τ gwr,Myr .…”
Section: Simulations Of the Second Sn In Dnsmentioning
confidence: 99%
“…These velocities can be combined with the merger time for the DNS system to estimate the offset distance of the future DNS merger (short GRB) from its birth place in the Galactic disk (e.g. Bloom et al 1999;Perna & Belczynski 2002;Voss & Tauris 2003;Fong et al 2010;Kelley et al 2010;Beniamini et al 2016b). Assuming, as a first-order approximation, constant motion throughout a galactic potential, an upper limit for this distance can be simply estimated as: d pc ≃ v km/s · τ gwr,Myr .…”
Section: Simulations Of the Second Sn In Dnsmentioning
confidence: 99%
“…Tsujimoto & Nishimura (2015) showed that MR-SNe can explain the early growth of Eu in dwarf spheroidal galaxies for [ ] < -Fe H 2 by assuming an event rate of about 0.5% of CC-SNe, while NSMs have problems with doing so. Observation of ultra-faint galaxies (Ji et al 2016;Roederer et al 2016) requires rare r-process events with large mass ejection, for which MR-SNe can be a source as well as NSMs (Beniamini et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The rate F UFD 0 implies that the probability of a NS disruption in a single UFD is about 0.1, which explains the uneven distribution. The amount of r-process material supplied by a single event, ∼0.1 M ⊙ , is more than sufficient to explain the observations [21,22,73]. Only a small fraction ∼ðv UFD =v ∞ Þ ∼ 10 −3 of the produced r-process material is likely to remain in the shallow gravitational potential well of a UFD because it is produced with a velocity v ∞ ∼ 0.1v esc .…”
Section: Prl 119 061101 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 95%
“…Observations imply that 1 in 10 UFDs have been a host to r-process nucleosynthesis events, which must, therefore, be rare [21,22,73]. The rate F UFD 0 implies that the probability of a NS disruption in a single UFD is about 0.1, which explains the uneven distribution.…”
Section: Prl 119 061101 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
See 1 more Smart Citation